PERANAN PROMOSI PRODUK DAN PELAYANAN KLIEN DALAM RANGKA PENINGKATAN PENDAPATAN USAHA PADA SASH BEAUTY STUDIO DI KOTA DENPASAR - Netrawati, I Gusti Ayu Oka; Permadi, I Gusti Agung Didit Eka; Oktiani, Asri; Fitri, Syarifah Massuki; Sari, Ni Wayan Nadia; Yuliartika, Dina; Shanianingrat, Shanianingrat (LPPM Institut Pendidikan Nusantara Global, 2024)
One of the rapid developments in the business world in Indonesia is in the beauty sector. This condition is characterized by intense business competition in the beauty sector. The increasing external need of humans is to always want to appear perfect in various circumstances. This is an incentive for the beauty business to continue to grow rapidly because demand for beauty continues to increase. Sash Beauty Studio which is located on Jalan Kaliasem No. 14 Denpasar Timur is business participating salon services give color in competition beauty salon services in Denpasar City with put forward promotion through narrated experience​ by clients/customers. Because service best ever​ he obtained so that enhancement income business service the salon can keep going increase. The marketing strategy that must be maintained based on the results of the SWOT analysis evaluation by Sash Beauty Studio and which has the most influence on the development of its business is the marketing strategy through social media Instagram and Facebook , namely uploading the results of make up and other beauty care activities in its salon as well as word of mouth or online marketing strategies such as mouth to mouth. Sash Beauty Studio is best intertwine work the same partnership with company cosmetics and wedding organizer in Denpasar City.